1998
DOI: 10.1152/ajpgi.1998.275.3.g449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endotoxin on gastric injury from luminal irritants in rats: potential roles of nitric oxide

Abstract: The expression and function of inducible nitric oxide synthase (iNOS) in the stomach is unclear. This study assessed the effects of endotoxin on rat gastric iNOS expression and its role in gastric injury from luminal irritants. In conscious rats, a 5-h treatment with intraperitoneal lipopolysaccharide (LPS; 1–20 mg/kg) dose dependently increased gastric mucosal iNOS immunoreactivity and increased gastric luminal nitrate and nitrite accumulation (Griess reaction). LPS also increased gastric luminal fluid accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 27 publications
5
35
0
Order By: Relevance
“…We confirmed previous findings that LPS elicits production of both pro-and antiinflammatory cytokines that favors a pro-inflammatory response as measured by the serum IL-6/IL-10 ratio [18]. We also confirmed that this inflammatory response is accompanied by elevated levels of serum hepatocellular enzymes which we have previously shown to correlate with liver injury according to histological assessment and F-actin analysis [19,20,31,32]. In these previous studies, we also reported that LPS-induced hepatic injury was mediated, at least in part, by upregulation of hepatic COX2 and iNOS, as selective inhibition of these two proteins diminished hepatic injury from LPS [19,20,[33][34][35].…”
Section: Discussionsupporting
confidence: 90%
“…We confirmed previous findings that LPS elicits production of both pro-and antiinflammatory cytokines that favors a pro-inflammatory response as measured by the serum IL-6/IL-10 ratio [18]. We also confirmed that this inflammatory response is accompanied by elevated levels of serum hepatocellular enzymes which we have previously shown to correlate with liver injury according to histological assessment and F-actin analysis [19,20,31,32]. In these previous studies, we also reported that LPS-induced hepatic injury was mediated, at least in part, by upregulation of hepatic COX2 and iNOS, as selective inhibition of these two proteins diminished hepatic injury from LPS [19,20,[33][34][35].…”
Section: Discussionsupporting
confidence: 90%
“…The mechanism of this protection is attributed primarily to its potent vasodilatory action, which leads to the improvement of mucosal circulation; however, excessive nitric oxide production can be toxic to gastric mucosa (53,54). The expression of iNOS was not affected by GGA itself or by ethanol-induced mucosal damage, but the expression of nNOS increased in the experimental rats at 5 hours after GGA administration, suggesting that nNOS contributes to the delayed protection afforded by GGA.…”
Section: Discussionmentioning
confidence: 94%
“…28,29 On the other hand, the excessive production of NO can be toxic to the gastric mucosa. 30,31 NO is known to play an important role in the regulation of the synthesis and secretion of gastric mucin. [20][21][22][23] The present experiments were designed to confirm that NO stimulates mucin synthesis in gastric pit cells.…”
Section: Discussionmentioning
confidence: 99%